2021
DOI: 10.1080/07391102.2021.1905551
|View full text |Cite
|
Sign up to set email alerts
|

Identification of doxorubicin as a potential therapeutic against SARS-CoV-2 (COVID-19) protease: a molecular docking and dynamics simulation studies

Abstract: After one year, the COVID-19 pandemic caused by SARS-CoV-2 is still the largest concern for the scientific community. Of the many recognized drug targets of SARS-CoV-2, the main protease is one of the most important target due to its function in viral replication. We conducted an in silico study with repurposing drugs of antibiotics class against virus protease and peptidase using AutoDock tool. The following significant binding energy interaction was observed with protease (PDB: 6LU7) like piperacillin –7.25;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Doxorubicin is a chemotherapeutic agent treating various types of cancer [ 143 ]. A study of structural bioinformatics revealed that doxorubicin proved the significant binding energy with SARS-CoV-2 main protease in the molecular docking [ 144 ]. This result suggested that doxorubicin could be a potential drug to treat severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin is a chemotherapeutic agent treating various types of cancer [ 143 ]. A study of structural bioinformatics revealed that doxorubicin proved the significant binding energy with SARS-CoV-2 main protease in the molecular docking [ 144 ]. This result suggested that doxorubicin could be a potential drug to treat severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…two main amino acid residues also involved in the interaction of N3 inhibitor with the same protease target [56,65]. Interestingly, these two residues were also previously associated with the interaction of other molecules investigated as anti-COVID-19 drugs and endowed with M pro inhibitory activity [66,67].…”
Section: Compoundmentioning
confidence: 83%
“…We examined the astragalin-protease complex structure for the pose with the lowest binding energy by the ProteinPlus software and noticed that the plant compound was involved in multiple H-bonding, with residues Phe140 and Glu166 of the viral protein, two main amino acid residues also involved in the interaction of N3 inhibitor with the same protease target [56,65]. Interestingly, these two residues were also previously associated with the interaction of other molecules investigated as anti-COVID-19 drugs and endowed with M pro inhibitory activity [66,67].…”
Section: Resultsmentioning
confidence: 99%
“…Qazi et al. used Autodock to conduct computer simulations of the antibiotic class of viral proteases and peptidases and found that doxorubicin can be used to inhibit viral proteases that may prevent entry into host cells to control the COVID‐19 disease [ 45 ]. Bragi Lovetrue built an accurate COVID‐19 disease model.…”
Section: Discussionmentioning
confidence: 99%